Designing policy instruments for regional floodplain management in Austria: the role of effectiveness and legitimacy. Issue 6 (2nd November 2022) - Nordbeck, Ralf; Löschner, Lukas; Seher, Walter
ABSTRACT : This article explores the issue of regional floodplain management in Austria from a policy design perspective. Austria has experienced a series of major floods in recent years. In response to these flood events a range of policy instruments at the land–water nexus were developed. Three policy instruments were selected as case studies to represent this policy shift toward integrated flood risk management: (a) regulatory spatial planning, (b) water associations and (c) financial compensation schemes for flood storage. The main objective of our article is to build a better understanding of the interlinkage of effectiveness and legitimacy in the process of policy formulation. The analysis draws on a review of policy documents and expert interviews with core decision-makers. Our analysis shows that the main challenge in the selection process is not the issue of effectiveness, but rather the acceptance of the policy instrument by target groups. Stakeholder participation increases the legitimacy of the instrument design and minimizes conflicts in the following implementation, thereby increasing the effectiveness of the policy instrument. In contrast to the assumptions prevailing in the current policy design literature, our empirical analysis does not support the common preposition that participatory processes result in inferior forms of policy design.